Pengaruh Supervisor Support, Work Engagement, dan Turnover Intention Terhadap Kepuasan Kerja pada Perusahaan Daerah Air Minum (PDAM) Tirtauli Pematangsiantar - Laura Natasya Pandiangan; Elperida Sinurat; Kristanty Nadapdap (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to determine and analyze the influence of supervisor support, work engagement, and turnover intention on job satisfaction at the Regional Drinking Water Company (PDAM) Tirtauli Pematangsiantar. The sample in this study was 71 respondents. Based on the results of the t hypothesis test, the t value of supervisor support was 5.082> t table 1.996, and the significance value was 0.000 <0.05, so partially supervisor support had a significant effect on job satisfaction, the t value of work engagement was 3.110> t table 1.996, and the significance value was 0.003 <0.05, so partially work engagement had a significant effect on job satisfaction, the t value of turnover intention was -0.988 <t table 1.996, and the significance value was 0.327> 0.05, so partially turnover intention had no effect and was not significant on job satisfaction. Based on the results of the F hypothesis test, the calculated F value is 69.910> 2.74 and the significance value of F is 0.000 <0.05, so that simultaneously supervisor support, work engagement, and turnover intention have a significant effect on job satisfaction. Based on the results of the determination coefficient analysis, the Adjusted R-Square value is 0.747 or 74.7%, meaning that the influence of supervisor support, work engagement, and turnover intention on job satisfaction is 74.7%